2022
DOI: 10.3390/microorganisms10112234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fe2+ and Shear Stress on the Development and Mesoscopic Structure of Biofilms—A Bacillus subtilis Case Study

Abstract: Bivalent cations are known to affect the structural and mechanical properties of biofilms. In order to reveal the impact of Fe2+ ions within the cultivation medium on biofilm development, structure and stability, Bacillus subtilis biofilms were cultivated in mini-fluidic flow cells. Two different Fe2+ inflow concentrations (0.25 and 2.5 mg/L, respectively) and wall shear stress levels (0.05 and 0.27 Pa, respectively) were tested. Mesoscopic biofilm structure was determined daily in situ and non-invasively by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The comparison of the results of the three experiments showed that Na + , Fe 3+ and Fe 2+ did not affect cell activity, which was similar to the conclusion of previous studies. 38,54 This study demonstrated that the prepared curved vascular scaffold could be used to explore the mechanism of vascular tortuosity leading to lesions in vitro. The Fe 3+ ions introduced by immersion during the preparation and the Fe 2+ ions obtained by light reduction had no effect on the cellular activity.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The comparison of the results of the three experiments showed that Na + , Fe 3+ and Fe 2+ did not affect cell activity, which was similar to the conclusion of previous studies. 38,54 This study demonstrated that the prepared curved vascular scaffold could be used to explore the mechanism of vascular tortuosity leading to lesions in vitro. The Fe 3+ ions introduced by immersion during the preparation and the Fe 2+ ions obtained by light reduction had no effect on the cellular activity.…”
Section: Discussionmentioning
confidence: 80%
“…The comparison of the results of the three experiments showed that Na + , Fe 3+ and Fe 2+ did not affect cell activity, which was similar to the conclusion of previous studies. 38,54…”
Section: Discussionmentioning
confidence: 99%
“…The structure of calcium is very important in agricultural soil, because there is a complex adsorption of Ca 2+ ions in groundwater which must be quite high (Amin, 2016). The researchers have conducted research on liquid waste for the concentration of Fe 2+ in human water and other living things under certain conditions it requires iron (Fe) as a nutrient but excessive levels need to be avoided (Gierl et al, 2022;Eisele & Gabby, 2014;Ondigo et al, 2013). So far, several methods have been used to determine the concentration of Ca 2+ and Fe 2+ ions such as coagulation and adsorption in water but at a high cost and takes a long time (Ngteni et al, 2020;Mu et al, 2017;Tiwow et al, 2017;Zheng et al, 2020;Kyomugasho et al, 2017).…”
Section: Introductionmentioning
confidence: 99%